Microencapsulated and Fresh Royal Jelly: Monitoring 10-HDA Content, Antibacterial and Antifungal Activity at Different Storage Periods - Ulubayram, Neslihan; Cinar, Aycan Yigit (Inst Tecnologia Parana, 2023)
Royal Jelly (RJ) is a unique functional food having rich nutrient composition. Due to its extremely sensitive and perishable nature, the cold chain is inevitable to maintain the biological properties of RJ. Microencapsulation is considered as an alternative technology for commercial RJ forms, owing to the elimination of cold-chain requirements. The objective of the study is to evaluate the microencapsulation of RJ and its protective effect on the 10-HDA content as well as on the antimicrobial activity during a defined storage period. Microcapsules were formed by utilizing alginate cross-linking technique in the encapsulator (Buchi B-390, Flawil, Switzerland) under 450 mbar. The antibacterial and antifungal activity of fresh and microencapsulated royal jelly (MRJ) was examined, comparatively. The possible changes in antimicrobial activity in the 1st, 3rd, and 6th months were evaluated considering the changes in 10-HDA levels. The antimicrobial efficiency of RJ on test bacteria (Micrococcus luteus, Staphylococcus epidermis, Salmonella Enteritidis, Escherichia coli) and yeast (Candida albicans, Candida parapsilosis) was maintained throughout the storage period. On the other hand, antifungal activity on test molds (Penicillium digitatum, Aspergillus flavus) slightly decreased from the 3rd month. No significant difference between 10-HDA contents was observed until the end of storage (p>0.05). The results indicate that microencapsulation retains the 10-HDA content of RJ for six months and is a promising method enabling storage at room temperature.
Keywords: 10-HDA; antibacterial; antifungal; microencapsulation; royal jelly; storage